CLONAL PROPAGATION OF CAMPTOTHECA ACUMINATA THROUGH SHOOT BUD CULTURE. - JAIN, ASHOK K.
The chinese tree Camptotheca acuminata produces the anti-cancer and anti-retroviral drug camptothecin. Methods were developed for the clonal propagation of this important medicinal plant through shoot bud culture. Shoot buds were excised from 25 to 30 day old seedlings, presoaked for 48 h in three different liquid media containing either BA (2.22-17.4,µM), kinetin (2.32-18.58 µM), or thidiazuron (0.1-10,µM) and were subsequently cultured on semi-solid medium of the same composition. Multiple shoots only developed from the 6-benzyladenine presoaked explants with the maximum number of shoots initiated from buds presoaked in and grown on B5 medium containing 17.4 µM 6-benzyladenine. Individual shoots were removed from clusters and rooted on B5 supplemented with in-dok-3-butyric acid (4.9-19.6,µM). The lowest concentration of indole-3-butyric acid (4.9,µM) gave the highest percentage of rooting (82%) and the shortest root initiation period (18 d). Over 90% of the in vitro rooted planteas surv